Pengaruh Pengelolaan dan Pemanfaatan Sarana Prasarana Terhadap Efektivitas Kerja Pegawai Badan Pemeriksa Keuangan - M. Falih Windi Iqram Nugroho; Firmansyah; Rosy Armaini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to examine how the management and use of facilities and infrastructure affects the productivity of workers at the Audit Board of the Republic of Indonesia (BPK) Representative Office of South Sumatra Province. Thirty respondents make up the study's population. Employees of the BPK Representative Office of South Sumatra were given questionnaires as part of the quantitative survey research methodology. Multiple linear regression was used to examine the data using the SPSS software. The findings of the partial test demonstrate that infrastructure and facilities management significantly and favorably affects employee productivity. Similarly, the efficacy of employees' work is positively and significantly impacted by the use of infrastructure and amenities. The findings of the simultaneous test show that employee job effectiveness is positively and significantly impacted by both facility and infrastructure management and usage.